2018
DOI: 10.1021/jacs.7b08729
|View full text |Cite
|
Sign up to set email alerts
|

Large Converse Piezoelectric Effect Measured on a Single Molecule on a Metallic Surface

Abstract: The converse piezoelectric effect is a phenomenon in which mechanical strain is generated in a material due to an applied electrical field. In this work, we demonstrate the converse piezoelectric effect in single heptahelicene-derived molecules on the Ag(111) surface using atomic force microscopy (AFM) and total energy density functional theory (DFT) calculations. The force-distance spectroscopy acquired over a wide range of bias voltages reveals a linear shift of the tip-sample distance at which the contact b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…Previously performed density functional theory (DFT) calculations for AT [7]H on Ag(111) showed that a sulphur atom gets pinned to a single Ag surface atom. 14 The proximal phenanthrene groups, however, show a similar distance (3 Å) to the surface as plain [7]H on various surfaces, 12 suggesting an additional surface binding through that group. DFT calculations for [5]H on Cu(111) 24 and db [7]H on Ag(111) 28 showed that the C6 rings of the proximal phenanthrene group tend to be placed above threefold hollow sites.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Previously performed density functional theory (DFT) calculations for AT [7]H on Ag(111) showed that a sulphur atom gets pinned to a single Ag surface atom. 14 The proximal phenanthrene groups, however, show a similar distance (3 Å) to the surface as plain [7]H on various surfaces, 12 suggesting an additional surface binding through that group. DFT calculations for [5]H on Cu(111) 24 and db [7]H on Ag(111) 28 showed that the C6 rings of the proximal phenanthrene group tend to be placed above threefold hollow sites.…”
mentioning
confidence: 98%
“…10 Beyond chiral recognition, the surface self-assembly of helical aromatic hydrocarbons, so-called helicenes, is motivated by studying novel physical effects, such as chiroptical responses, electron spin selectivity or molecular electro-mechanics. [11][12][13][14] Consequently, synthesis and functionalization of surfaces with helicenes has received increasing attention recently. [15][16][17] There have been several reports on the fate of chiral crystallization of helicenes on various surfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing interest in the electromechanical response of organic and biomaterials, 5,[32][33] and computational design of peptides with increased response will guide efforts to produce new active materials for applications including touch and force sensors, and electroactive actuators.…”
Section: Discussionmentioning
confidence: 99%
“…The piezoelectric effect is the linear electromechanical interaction between mechanical and electrical states in certain solid materials ( Figure a) . In this way, piezoelectric materials can be used to harvest mechanical energy and convert it into electricity through a mechanical‐to‐electrical transformation mechanism .…”
Section: Materials For Energy Conversion Devicesmentioning
confidence: 99%